Ginsenoside extract from ginseng extends lifespan and health span in Caenorhabditis elegans. Issue 15 (10th June 2021) - Wang, Hui; Zhang, Shuai; Zhai, Lu; Sun, Liwei; Zhao, Daqing; Wang, Zeyu; Li, Xiangyan
Abstract : Ginsenoside extract from ginseng extends lifespan and health span in Caenorhabditis elegans through activating NRF2/SKN-1, SIRT1/SIR 2.1, and FOXO/DAF-16 signaling pathways. Abstract : Nutrition intervention has become a potential strategy to improve healthspan and prolong lifespan. Ginseng has been used for thousands of years and developed as a functional food to provide various protective effects to humans. An extract of total ginsenosides (TGS), a mixture of the main active ginsenosides from ginseng, has wide biological activities and health benefits for age-related diseases, including antioxidation and improvements in mitochondrial function. However, the molecular mechanism of TGS for prolonging lifespan and improving fitness and how exactly this is achieved under normal and stress conditions remain largely unclear. In this study, wild-type and mutant C. elegans strains are used to investigate the role and molecular mechanism of TGS-mediated longevity, health benefits, and stress resistance. The results showed that treatment with TGS at 0.2 mg mL −1 from the stage of day four to death significantly extended the lifespan of worms by 14.02% without effects on bacterial metabolism and food intake. Furthermore, TGS treatment obviously improved age-associated mobility, muscle fiber organization, lipofuscin accumulation, and enhanced resistance under oxidative stress. Importantly, these effects of TGS were achieved by activating the signaling pathways of anti-oxidant regulation and longevity, including the NRF2/SKN-1, SIRT1/SIR 2.1, and FOXO/DAF-16 signaling pathways. Finally, it was found that Rg1, Re, and Rb1 were the major effective components of anti-oxidative activity and longevity. Collectively, the protective effect of ginsenoside extract in healthy aging and stress responses provides new insights for the development and practical application of ginseng functional products.